Development of the skiing organisation in Lvov between 1919-1939 - Leon Rak (Jan Długosz University in Częstochowa, 2020)
The aim of the article was to present the contribution of Lvov's skiers to the development skiing in Poland. There were described conditions of the skiing in Lvov especially terrain and climate conditions and the development of the skiing organisation's activity between 1919-1939. The terrain in Lvov and nearest neighbourhood was advantageous but climate often made skiing difficult. The skiing developed dynamically and it was popular in different social environments including also national minority groups. The Jewish skiing organisation cooperated with Polish under the Polish Ski Federation but Ukrainians were outside of the federation. The article includes also quantitative indicators of the development skiing in Lvov in the context of the Polish Ski Federation total data. Lvov's skiers were in great number between members of the Polish Ski Federation and their quantity tended to rising between 1932-1939. In the late 1930s the amount of ski competitors decreased in comparison to all members of the Lvov's skiing societies. This trend indicated faster increase the amount of recreational and tourist skiers than competitors.